Comparative study of the magnetic properties of La3Ni2B'O9 for B' = Nb, Taor Sb - Chin, C; Battle, P; Blundell, S; Hunter, E; Lang, F; Hendrickx, M; Paria Sena, R; Hadermann, J (Elsevier, 2017)
Polycrystalline samples of La 3 Ni 2 NbO 9 and La 3 Ni 2 TaO 9 have been characterised by X-ray and neutron diffraction, electron microscopy, magnetometry and muon spin relaxation (µSR); the latter technique was also applied to La 3 Ni 2 SbO 9 . On the length scale of a neutron diffraction experiment, the six-coordinate sites of the monoclinic perovskite structure are occupied in a 1:1 ordered manner by Ni and a random ⅓Ni/⅔B′ mixture. Electron microscopy demonstrated that this 1:1 ordering is maintained over microscopic distances, although diffuse scattering indicative of short-range ordering on the mixed site was observed. No magnetic Bragg scattering was observed in neutron diffraction patterns collected from La 3 Ni 2 B′O 9 (B′ = Nb or Ta) at 5 K although in each case µSR identified the presence of static spins below 30 K. Magnetometry showed that La 3 Ni 2 NbO 9 behaves as a spin glass below 29 K but significant short-range interactions are present in La 3 Ni 2 TaO 9 below 85 K. The contrasting properties of these compounds are discussed in terms of their microstructure.